Knowledge and attitude about leprosy among medical students and interns at tertiary care centre of central India: a cross-sectional study - Jadhao, Ashok R.; Tayade, Hitesh C.; Kherde, Abhijit N.; Dambhare, Punam M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Leprosy has been known to the Indians since the Vedic period. Leprosy is synonymous with social stigma due to reasons like mystery around its transmission, lack of knowledge on available treatment, deformities and religious views. Prejudice and lack of knowledge about leprosy exist even among medical practitioners and healthcare professionals around the world. Considering above mentioned facts, this study was conducted to study knowledge and attitude of medical students and interns towards leprosy. Methods: A cross-sectional study was conducted at IGGMC, Nagpur, among Third MBBS part one of 7th semester medical students who were exam going for community medicine and interns of IGGMC between October 2018 to January 2019. Questionnaire comprised of 27 knowledge-based and 22 attitude–oriented questions. In all total 210 subjects, 99 Interns and 111 students were enrolled for the study. Results: Mean age of interns was 23.52±0.66 years and that of students was 21.45±0.85 years. There was no significant difference in knowledge regarding cause and modes of transmission and clinical features of leprosy between interns and student however interns were having significant higher knowledge regarding diagnosis, treatment, prevention of deformity limitation and precaution to be taken against leprosy. Only 13(6.19%) participants were having knowledge regarding targets of NLEP that was to be achieved by year 2017. Though both interns and students both showed good attitude towards leprosy but only 34 interns and 31 students had ever rendered service or donated money for cause of leprosy. Conclusions: Knowledge regarding national program is limited in both groups, curriculum should be strengthen pertaining to National program.